2001
DOI: 10.1002/jqs.658
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dinoflagellate cysts in the Canadian Arctic marine region

Abstract: The Canadian Arctic is a major gateway for transport of freshwater from the Arctic Ocean to the North Atlantic. This region comprises the Beaufort Sea, the Canadian Arctic Archipelago (CAA) and northern sections of Baffin and Hudson bays. Subregional differences include major freshwater runoff to the Beaufort Sea and Hudson Bay, presence of Pacific and Atlantic Intermediate water in the west, and Atlantic Water in Baffin and Hudson bays. Principal component analysis of 50 core-top samples shows four subregiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 32 publications
5
66
1
Order By: Relevance
“…Halodinium minor has been previously reported from polar environments by Mudie (1992) and from warm to temperate environments in Australian estuaries by McMinn (1991). Matthiessen (1995) found high relative abundances at the Greenland and Iceland shelf with a random occurrence in the central Greenland Sea and the Norwegian Sea.…”
Section: Dinocyst Assemblagesmentioning
confidence: 75%
See 2 more Smart Citations
“…Halodinium minor has been previously reported from polar environments by Mudie (1992) and from warm to temperate environments in Australian estuaries by McMinn (1991). Matthiessen (1995) found high relative abundances at the Greenland and Iceland shelf with a random occurrence in the central Greenland Sea and the Norwegian Sea.…”
Section: Dinocyst Assemblagesmentioning
confidence: 75%
“…Cyst assemblages in coastal environments are usually tolerant to a wide range of temperatures and salinities and reflect more distinctive ecological preferences such as oceanic versus coastal waters, nutrient availability, salinity gradients as well as stress tolerance to rapid and periodic changes (e.g. Mudie, 1992;Dale et al, 2002;Harland et al, 2004;Radi et al, 2007;and Price and Pospelova, 2011). Dinoflagellate cysts are composed of highly resistant refractory organic matter and generally well preserved in sediments.…”
Section: G Milzer Et Al: Benthic Foraminiferal Stable Isotopes and mentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this might indicate either a lower degree of metabolic activity or a high degree of dormancy of these taxa (Jones & Lennon, 2010). During immediate microscopic investigations, we found many dinoflagellate cysts (data not shown), which are known to be present in Arctic waters (Harland et al, 1980;Mudie & Rochon, 2001;Potvin et al, 2013) at unfavourable conditions. Other studies also found a very high amount of Alveolata (alveolates) in their DNA libraries (Massana & Pedros-Alio, 2008;Not et al, 2009), although they were not investigating the rRNA library.…”
Section: Phototrophic Community Of Arctic Fyi and Myimentioning
confidence: 79%
“…Dinocysts are particularly useful microfossils in high latitudes because they are especially sensitive to sea-surface conditions in Arctic and sub-Arctic areas (e.g. Kunz-Pirrung, 2001;Matthiessen et al, 2005;Mudie and Rochon, 2001;Radi et al, 2001;de Vernal et al, 2001de Vernal et al, , 2005. Furthermore, dinocysts are preferentially preserved in environments like the Mackenzie Trough where sediment accumulation rates are relatively high, which prevents oxidation.…”
Section: Introductionmentioning
confidence: 99%